Uncovering the Anti-Herpetic Activity of Anionic Peptides Derived From the Cytoplasmic Domain of Nectin-1 - Rakesh Rahangdale; Sumit Birangal; Gautham Shenoy; Fayaz Shaik Mohammad; Mukesh Pasupuleti; Raghu Chandrashekar Hariharapura (Bioinformatics and Biology Insights)
Nectin-1/herpes simplex virus glycoprotein D (HSV gD) interaction is crucial to drive herpes simplex virus (HSV) entry. Polyanions are known to show great potential as antivirals. Thus, we explored a peptide-based biotherapeutic approach and, for the first time, evaluated an anionic peptide derived from nectin-1 designed to bind HSV gD. Peptides enriched in acidic and basic residues were selected and computationally modeled using PEP-FOLD3, PROCHECK, ClusPro 2.0, and Desmond. Their antiviral efficacy was tested through virucidal, cell pretreatment, attachment inhibition, entry inhibition, and cytopathic effect (CPE) inhibition assays using a 10 TCID 50 (Tissue Culture Infectious Dose 50%) viral dose. Among 4 designed peptides, C1 and C2 showed strong binding to HSV-1 and HSV-2 gD in molecular dynamic (MD) simulations. Peptide C1 exhibited significant virucidal activity (HSV-1: 64.92%, HSV-2: 67.16%), attachment inhibition (HSV-1: 62.03%, HSV-2: 59.38%), and host cell-entry inhibition (HSV-1: 71.37%, HSV-2: 76.28%) at 250 µg/mL concentration. Combination treatment with peptides C1 and C2 at a final concentration of 250 µg/mL (125 µg/mL each) exhibited an additive effect against HSV-1 (68.57%) and HSV-2 (73.37%) infections when tested by CPE inhibition assay. This highlights the potential of HSV gD-targeted anionic peptides for future anti-HSV therapeutics.